The causal effects of R&D grants: Evidence from a regression discontinuity - Pietro Santoleri; Andrea Mina; Alberto Di Minin; Irene Martelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
Direct public support for business R&D is a well-established remedy to market failures, yet empirical evidence on its effectiveness yields conflicting results. The paper investigates the impact of the first European public R&D grant program targeting small and medium enterprises (i.e. the SME Instrument) on a wide range of firm outcomes. We leverage the assignment mechanisms of the policy and employ a sharp regression discontinuity design to provide the broadest quasi-experimental evidence on R&D grants over both geographical and sectoral scopes. Results show that grants trigger sizable impacts. They increase investment, notably in intangibles, and innovation outcomes as measured by cite-weighted patents; they trigger faster growth in assets, employment and revenues; they lead to higher likelihood of receiving follow-on equity financing and lower failure chances. These effects tend to be larger for firms that are smaller and younger, or operating in sectors characterized by higher financial frictions. Furthermore, responses are stronger in countries and regions with lower economic development. The paper provides extensive evidence that the beneficial effects of R&D grants materialize through funding rather than certification effects.
Keywords: D22; G24; G32; L53; O31; 330; Regression discontinuity design; Research and development; Innovation Policy; SMEs